Prospective study of hemoglobin A1c and incident carotid artery plaque in Chinese adults without diabetes - Renying Xu; Ting Zhang; Yanping Wan; Zhuping Fan; Xiang Gao (Cardiovascular Diabetology, 2019)
Abstract Background Diabetes has been reported to be associated with carotid artery plaque (CAP). However, it remains unclear whether hemoglobin A1c (HbA1c) level, a marker for long-term glycemic status, is associated with altered CAP risk in individuals with fasting blood glucose (FBG) concentrations below the current cutoff for diabetes. Methods Included were 16,863 Chinese adults (aged 18 years or more; 9855 men and 7008 women) with fasting blood glucose < 7.0 mmol/L at baseline (2013). Both HbA1c level and CAP (assessed via ultrasound B-mode imaging) were annually assessed during 2014–2018. All the participants were further classified into three groups based on baseline HbA1c level: ≤ 5.6%, 5.7–6.4%, and ≥ 6.5%. We used Cox proportional-hazards model to evaluate the association between HbA1c level and incident CAP, adjusting for a series of potential confounders. Results During 5 years of follow up, 3942 incident CAP cases were identified. Individuals with higher baseline HbA1c had higher future risk of CAP (p-trend < 0.001). In the full-adjusted model, each percent increase of HbA1c was associated with a 56% (HR = 1.56, 95% CI 1.37, 1.78) higher risk of CAP. Excluding participants with chronic inflammation, as assessed by high-sensitivity C-reactive protein and white blood cell, and those with FBG ≥ 5.6 mmol/L at baseline generated similar results. Conclusions Elevated HbA1c level was associated with high risk of developing CAP in Chinese adults without FBG defined diabetes.